Factors influencing customers’ switching intentions to new energy vehicles based on the push-pull mooring model using SEM-ANN approach in Shanxi, China - Zhang Juanjuan; Ratneswary Rasiah (Scientific Reports)
Abstract This study applied the Push-Pull Mooring (PPM) theoretical framework to investigate how push, pull, and mooring factors influence sustainable transportation choices. The main objective is to explore which push, pull, and mooring factors significantly influence the intention to switch from conventional vehicles to NEVs. The study utilized the SEM-ANN approach based on a dataset of 822 participants collected in Shanxi, China. Results show that environmental concern and dissatisfaction with traditional vehicles (push factors), along with perceived convenience, subjective norms, and alternative attractiveness of NEVs (pull factors), positively influence switching intentions. Conversely, switching costs and habit (mooring factors) negatively impact the switching intention. Inertia was found to negatively moderate the relationship between environmental concern, subjective norms, and switching intention. Thus, these findings provide valuable insights for Shanxi’s transition to low-carbon transportation.